Concepções de leitura em práticas de letramento na educação de jovens e adultos do meio rural - Giane Maria da Silva (2008)
The purpose of this research was to know the reading conceptions of four teachers that work at beginning level of Adult and Youth Education, in three rural communities of Caeté, in the metropolitan region of Belo Horizonte, MG. The study is based on the reading scholarly practices and on the teachers expectations and representations about writing, particularly about reading, trying to stablish the relations between the scholarly practices and the specific culture context in which these institutions are located. First, it was described the uses and functions of the writing texts utilized in the classroom, as much as it was exposed the motivation to select them and the access to them. From the analysis of the reading conceptions of the teachers, it was taken into account their work conditions and school life. It was also presented a characterization of these teachers, trying to understand who they are and how they started to work with Adult and Youth Education. The investigation was realized into a qualitative approach, joining different strategies, like observation in the classrooms, notes in my camp diary and semi-structured interviews. The results obtained with this survey indicated that the work of reading, conducted by the teachers, had several gaps, e.g. lack of clarity on the goals, a very few variety of texts, no planning of the activities and inadequacy of the selected texts to the students` interests. Through this research, it was verifyed that the teachers` main objective is to decode the language. Finally, after analyzing the referred results, it became clear the necessity for a program of continuous formation that attends the interests and requirements of the adult and youths teachers.